To what extent do South Africa and Scotland comparatively respect, protect and fulfill children's rights in the context of youth justice and in light of their international and regional obligations? - Thomson, Gemma (Department of Public Law, 2016)
Juvenile justice is a core facet of international child law aimed at protecting children who come into conflict with the law. The international and regional juvenile justice frameworks outline the standards expected of States party to the international instruments. Both South Africa and Scotland are obligated to adhere to these rules and principles by way of creation and implementation of domestic laws in furtherance of a child-centered approach to justice. This dissertation analyses the effectiveness of both national systems and assesses the extent to which they respect, protect and fulfill children's rights in the context of international child law. This study also aims to highlight areas in which South Africa and Scotland fail to meet the prescribed standards and proposes various recommendations in order to do so more effectively.